Analisis Kestabilan Lubang Bukaan Dengan Pengujian Flat Jack Pada Dinding Tunnel 1 Tambang Bawah Tanah PT Allied Indo Coal Jaya, Sawahlunto - Mhd Hafiz Diska; Murad Murad (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. Geomechanical testing is very important in the mining industry, both open pit, and underground mining. Geomechanics testing aims to determine rock strength. Rock strength is a major determinant of slope stability in open mines or opening holes in underground mines. There are several geomechanical testing methods, based on their nature, geomechanical testing consists of non-destructive tests and destructive tests. Based on location, geomechanical testing consists of in situ tests and ex-situ tests. One example of in situ and non-destructive testing is flat jack testing. The flat jack method is a method based on the measurement of the pressure needed to restore the stress released. Flat Jack generates known stresses in rock mass. Flat jack testing is carried out on the underground mine wall to get the stress value. Based on the calculation of the safety factor of the underground mine of PT Allied Indo Coal Jaya, at location 1 the values of fk = 1.41 (tensile stress) and fk = 1.89 (compressive stress) are obtained. At location 2 the value of fk = 1.23 (tensile stress) and fk = 1.63 (compressive stress). At location 3 the value of fk = 1.23 (tensile stress) and fk = 1.63 (compressive stress).Keywords: Flat Jack, Geotechnical, Rock Stress, Safety Factor, Underground Mining.